2010
DOI: 10.3390/molecules15031898
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Phase Synthesis of Cyanuric Acid from Urea

Abstract: The focus of this paper was to identify a cheaper solvent from among diesel fuel, kerosene, sulfolane or a mixture of sulfolane and cyclohexanol for the preparation of cyanuric acid heterocyclization of urea. To obtain a higher yield, the effects of catalyst (sodium, ammonium, calcium and zinc salts) and temperature (160 °C to 220 °C) on the trimerization of urea were also carefully studied. We established the optimal reaction conditions and further validated them in our scale-up experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 4 publications
0
9
0
2
Order By: Relevance
“…An appropriate solvent for this reaction must fit the following principles: the solvent has a boiling point within the pyrolysis temperature range; it can dissolve the urea but do not or slightly the cyanuric acid; it can be well recovered and recycled . We finally choose the sulfolane–cyclohexanol (Scheme ) mixture as the solvent because it could provide an appropriate reaction temperature and the final product's purity was higher than the normal industrial method . It has been reported that the presence of ammonia produced by urea decomposition would cause a higher content of aminated by‐product .…”
Section: Resultsmentioning
confidence: 99%
“…An appropriate solvent for this reaction must fit the following principles: the solvent has a boiling point within the pyrolysis temperature range; it can dissolve the urea but do not or slightly the cyanuric acid; it can be well recovered and recycled . We finally choose the sulfolane–cyclohexanol (Scheme ) mixture as the solvent because it could provide an appropriate reaction temperature and the final product's purity was higher than the normal industrial method . It has been reported that the presence of ammonia produced by urea decomposition would cause a higher content of aminated by‐product .…”
Section: Resultsmentioning
confidence: 99%
“…Asam sianurat dengan rumus formula kimia C 3 H 3 N 3 O 3 atau C 3 N 3 (OH) 3 (gambar 2) dan nama IUPAC 1,3,5-triazinane-2,4,6-trione adalah oksitriasin analog melamin sebagai produk sampingan dalam sintesis melamin dan berbentuk kristal putih. Asam sianurat dapat digunakan untuk sintesis disinfektan, klorinasi air kolam renang (Downes et al, 1984), antioksidan (She et al, 2010), pelapis cat (Whitten and Lin, 1999), herbisida (Huthmacher and Most, 2005), plastik, polyester dan kosmetik (Chuenarrom et al, 2014) serta feed additive ruminansia (Barboza and Barrionuevo, 2007). trione;1,3,5-triazine-2,4,6-triamine adalah kompleks kristal yang terbentuk dari campuran melamin dan sianurat dengan perbandingan 1:1 (He et al, 2008).…”
Section: Asam Sianuratunclassified
“…Contamination of soils by melamine and cyanuric acid can occur through numerous pathways. Nitrogenous fertilizers can contain melamine and cyanuric acid, which can be a source of accumulation in soil, resulting in plant uptake and food chain transfer . For instance, urea can be thermally degraded to cyanuric acid, from which melamine can be formed . Nevertheless, no earlier studies have measured melamine or cyanuric acid in fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…22 For instance, urea can be thermally degraded to cyanuric acid, from which melamine can be formed. 23 Nevertheless, no earlier studies have measured melamine or cyanuric acid in fertilizers.…”
Section: ■ Introductionmentioning
confidence: 99%